Pemberdayaan Industri Rumahan Ceriping Gethuk untuk Meningkatkan Kuantitas Produksi dan Kemasan Produk (Packaging) - Aqidah Asri Suwarsi; Safaah Restuning Hayati; Syah Amelia Manggala Putri (Jurnal Pemberdayaan Masyarakat, 2022)
One of the gethuk centers in Magelang is in Sedayu village, Muntilan sub-district. The gethuk and ceriping craftsmen who are partners are Mr. Rohmat and Ms. Hanik. The main problem faced by partners is in the production process, both in chip production and gethuk production. Production is still done manually and inefficiently. Another problem faced by partners is packaging of Gethuk chip products. This gethuk chip is still manually packed with 'dislomoti' and affixing the brand to the packaging just by attaching the brand's writing, in the form of black and white paper into the package. The purpose of this service is to solve the problem of efficiency of the production process by petrifying the procurement of cutting machines. The second objective is to solve the problem of still simple product packaging that is overcome by the procurement of press machines to glue plastic packaging. After that, assistance and training in the packaging of gethuk chips with press machines and trademark affixing with plastic screen printing were carried out. The results of the service have succeeded in providing gethuk, press machines, and plastic packaging cutting machines that have been screened with brands and PIRT numbers. The presence of these machines succeeded in increasing the production volume significantly from 10-15 kg perday to 25 kg perday.